Water-based anticorrosive paint and preparation method thereof
By using water-based polyurethane resin and acrylic emulsion in water-based coatings and adding specific penetrants and dispersants, the problem of insufficient anti-corrosion performance of water-based coatings is solved, and the goal of high-performance environmentally friendly coatings is achieved.
Patent Information
- Application Number
- CN202411714081.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
Water-based coatings have weak corrosion resistance and are difficult to meet the market's demand for high-performance environmentally friendly coatings.
Water-based polyurethane resin and acrylic emulsion are used as the main film-forming substances, and specific penetration and dispersants are added to enhance the anticorrosion performance of the coating by improving the adhesion and durability between the coating and the substrate.
It significantly improves the anticorrosion performance of water-based anticorrosion coatings, reduces the possibility of coating peeling and corrosive media penetration, and improves the environmental protection performance and stability of the coatings.
Smart Images

Figure BDA0005156487550000011 
Figure BDA0005156487550000021 
Figure BDA0005156487550000041
Abstract
Description
Technical Field
[0001] The present application relates to the field of coating technology, and in particular to a water-based anti-corrosion coating and a preparation method thereof. Background Art
[0002] Traditional industrial coatings generally use organic solvents as dispersion media, which shows significant advantages in preparation process, storage conditions and transportation convenience.
[0003] However, with the continuous improvement of social awareness and the popularization of environmental protection concepts, people have begun to pay more attention to the environmental protection characteristics of materials. Organic solvents release a large amount of volatile organic compounds (VOCs) during use, which pose a threat to human health and the natural environment. In view of this, many research teams and companies at home and abroad have invested a lot of energy in research in order to find more environmentally friendly paint alternatives. Against this background, water-based paints came into being and quickly made significant progress and development.
[0004] Water-based paint, as the name implies, is a paint that uses water as a solvent. Due to its environmentally friendly characteristics, this new type of paint has been widely favored in the market. However, using water as a solvent also inevitably has some defects, such as its weak anti-corrosion performance. Summary of the invention
[0005] To solve the above-mentioned problems, the present application provides a water-based anti-corrosion coating and a preparation method thereof, aiming to combine the environmental advantages of water-based coatings with enhanced anti-corrosion performance to meet the market demand for high-performance environmentally friendly coatings.
[0006] In the first aspect, the present application provides a water-based anti-corrosion coating using the following technical solutions: A water-based anticorrosive coating, the raw materials used for preparation, measured by weight, include: The penetrant is prepared by the following preparation method: S1, weighing deionized water, anionic emulsifier, nonionic emulsifier, vinyl trimethoxy silane, and propylene glycol, then mixing them, and heating to 85-90° C. to obtain a kettle bottom material; S2. Deionized water, anionic emulsifier, and nonionic emulsifier are weighed separately, and after stirring and mixing, methyl methacrylate, butyl acrylate, methacrylic acid, and methacrylate phosphate monomers are added, and after stirring and mixing, an emulsion is obtained, and 5-10 wt% of the emulsion is taken out as a seed solution; S3. Add the seed liquid to the kettle bottom material at 85-90°C, add the ammonium persulfate aqueous solution dropwise after 1-2 minutes, stir and react for 10 minutes, add the remaining emulsion first, then add tert-butyl hydroperoxide, stir and react at 83-85°C for 3.5-4 hours, keep warm at 85°C for 1 hour, cool to 73°C, add the redox agent dropwise and keep warm for 20 minutes, continue to cool to below 40°C, adjust the pH value to 7-7.5, filter through 120 mesh, and obtain the product.
[0007] By adopting the above technical scheme: the water-based anti-corrosion coating uses water-based polyurethane resin and acrylic emulsion as main film-forming materials, both of which are water-based materials. Compared with traditional solvent-based coatings, the emission of volatile organic compounds (VOCs) is greatly reduced, thereby improving the environmental performance of the coating; In addition, by adding a specific penetrant, the coating can form a tight coating on the surface of the substrate, effectively resisting the rust of the substrate and improving the anti-corrosion performance of the coating. The methacrylate phosphate monomer in the penetrant can improve the adhesion between the coating and the substrate interface, making the coating and the substrate more tightly bonded, reducing the possibility of coating shedding and corrosive medium penetration.
[0008] Preferably, the raw materials used for preparation, by weight, include:
[0009] Preferably, the filler is one or more of kaolin, titanium dioxide, carbon black, barium sulfate, and wollastonite; and the other additives include one or more of a leveling agent, a thickener, and a pH adjuster.
[0010] Preferably, the anionic emulsifier is one of linear fatty alcohol sodium sulfate salt, fatty alcohol ether sulfate sodium salt, tridecyl ether sodium sulfate, sodium dodecyl sulfate, fatty phosphate, and alcohol ether succinic acid monoester sodium salt containing alkylphenol polyoxyethylene ether compounds; the nonionic emulsifier is one of tridecyl alcohol ethoxylate, octylphenol polyoxyethylene ether, and isomeric alcohol ethoxylate.
[0011] Preferably, the dispersant is a polyhydroxy stearic acid polyester salt, and is prepared by the following preparation method: Add 10-hydroxystearic acid monomer to a reactor, and carry out melt polycondensation under the conditions of 0.02-0.09Mpa and 123-134°C to form a polyester prepolymer; after the prepolymerization is completed, add a capping agent to the reactor, continue to react for 0.3-1h, then flow out, cool and dry to obtain a carboxyl-terminated polyester; then mix the carboxyl-terminated polyester with 6-amino-1-hexanol, add an alkali metal catalyst, heat at 61-64°C for reaction for 2.5-4h, purify after the reaction is completed to obtain a polyester derivative; disperse the polyester derivative in acetone, add an alkylating agent, stir at 45-51°C for reaction for 2-4h, and then purify to obtain a polyhydroxystearic acid polyester salt.
[0012] By adopting the above technical solution: the polyhydroxy stearic acid polyester salt contains a unique quaternary ammonium salt structure, the positive charge center of the quaternary ammonium salt structure can interact with the negative charge on the surface of the substrate to form a strong chemical bond, which helps to improve the adhesion between the coating and the substrate, making the coating more firmly attached to the surface of the substrate, and can also enhance the durability of the coating so that it can resist erosion and damage from the external environment.
[0013] In addition, the chemical structure of the Rhodia special monomer (methacrylate phosphate monomer) in the penetrant is highly compatible with the quaternary ammonium salt structure in the polyhydroxy stearic acid polyester salt dispersant. There may be interactions between them, such as hydrogen bonds, ionic bonds or van der Waals forces, which help to enhance the compatibility and synergy between the dispersant and the penetrant.
[0014] The dispersant thus prepared is used in combination with the above-mentioned penetrant and can exhibit excellent anti-corrosion performance in a variety of corrosive environments.
[0015] Preferably, the end-capping agent is one of docosatetraenoic acid, lauric acid, and palmitic acid; the alkylating agent is one of trimethyloxonium tetrafluoroborate and diethyl sulfate; the alkali metal catalyst is K 2 CO 3 、CSF-K 2 CO 3 One of them.
[0016] In a second aspect, the present application provides a method for preparing a water-based anti-corrosion coating using the following technical scheme: A method for preparing a water-based anticorrosive coating comprises the following steps: a. Mix waterborne polyurethane resin and acrylic emulsion, heat to 45-50°C, stir for 30-40 minutes to obtain a mixture; b. Weigh other additives and disperse them in water to form a solution, then add filler and polydopamine to the solution, heat to 55-60°C, stir for 50-60 minutes to obtain a dispersion; c. Add the dispersion, penetrant and emulsifier to the mixture, stir at 45-50°C for 1.6-2h. During this process, add defoamer and film-forming aid in sequence every 15-20min, observe the number of bubbles, stop stirring, and let it stand until no bubbles are generated.
[0017] Preferably, in step c, the mass concentration of the solution is 3-10 g / L.
[0018] In summary, this application has the following beneficial effects: 1. The present application adds a specific penetrant so that the coating can form a tight coating on the surface of the substrate, effectively resist the rust of the substrate, and significantly improve the anti-corrosion performance of the coating. The methacrylate phosphate monomer in the penetrant can enhance the adhesion of the interface between the coating and the substrate, making the coating and the substrate more tightly bonded, reducing the possibility of coating shedding and corrosive medium penetration, and the quaternary ammonium salt structure in the dispersant polyhydroxy stearic acid polyester salt also plays a role in enhancing the durability and adhesion of the coating, and the combination with it further improves the anti-corrosion performance of the coating; 2. The preparation method of the water-based anticorrosive coating in the present application has clear steps and is easy to operate. The stability and consistency of the coating performance are ensured by accurately controlling the addition order and reaction conditions of each raw material, and the dispersion process of fillers and other additives is optimized, thereby improving the uniformity and stability of the coating; In addition, the addition of polydopamine further enhances the adhesion and durability of the coating, which not only improves production efficiency but also reduces production costs, providing strong support for the widespread application of water-based anti-corrosion coatings. DETAILED DESCRIPTION
[0019] The present application is further described in detail below in conjunction with the examples. Except for the special instructions below, the raw materials used in the present application are all common commercially available materials.
[0020] Table 1: Raw material manufacturers / specifications in the examples Example 1 A water-based anticorrosive coating, the raw materials and the corresponding amounts thereof are shown in the following table, and the coating is prepared by the following preparation method: a. First, a water-based polyurethane resin and an acrylic emulsion are added to a reaction kettle for mixing, and the temperature is slowly raised to 45-50° C. and maintained within this temperature range, and during the process, stirring is continued for 30-40 minutes to ensure full fusion to form a uniform and stable mixture; b. Next, weigh the other required additives and slowly disperse them in a certain amount of pure water. By adjusting the dispersion conditions, the additives are evenly distributed in the water to form a solution with a mass concentration of 3-10 grams per liter. Subsequently, the pretreated filler and polydopamine powder are added to the solution in sequence, and the temperature is raised to 55-60°C again. At this temperature, stir for 50-60 minutes to ensure that the filler and polydopamine can be fully dispersed and evenly mixed in the solution to form the final dispersion; c. Then, add the prepared dispersion, penetrant and emulsifier to the previously prepared mixture, maintain the system temperature in the range of 45-50°C, continue stirring, and control the time between 1.6-2 hours. During this process, in order to effectively control and reduce the generation of bubbles in the system, it is necessary to add appropriate amounts of defoaming agent and film-forming aid to the system in turn every 15-20 minutes. At the same time, pay close attention to the number of bubbles in the system. Through continuous observation and adjustment, until no bubbles are generated in the system, stop stirring at this time, let the system cool and stabilize naturally in a static state, and finally obtain the desired product.
[0021] Wherein, the filler is titanium dioxide and kaolin, the other auxiliary agent is a leveling agent, and the above-mentioned penetrant is prepared by the following preparation method: S1: 20 g of deionized water, 0.3 g of anionic emulsifier, 0.1 g of nonionic emulsifier, 1.5 g of vinyltrimethoxysilane and 3 g of propylene glycol were mixed and heated to 85° C. to obtain a kettle bottom material; S2: 13.8 g of deionized water, 0.7 g of anionic emulsifier, and 0.2 g of nonionic emulsifier were stirred and mixed, and then 25.5 g of methyl methacrylate, 23.2 g of butyl acrylate, 0.5 g of methacrylic acid, and 1 g of methacrylate phosphate monomer were slowly added at 600 r / min, and stirred and mixed to obtain an emulsion, and 5-10 wt% of the emulsion was taken out as a seed solution; S3: Add the seed liquid to the bottom of the kettle at 85°C. After 1 minute, add an aqueous solution of ammonium persulfate (0.2g ammonium persulfate and 10g deionized water) dropwise, and stir for 10 minutes. Add the remaining emulsion first, then add 0.05g tert-butyl hydroperoxide, stir for 3.5-4h at 83-85°C, keep warm at 85°C for 1h, cool to 73°C, add 0.03g redox agent VC dropwise, keep warm for 20min, cool to below 40°C, adjust the pH to 7-7.5, filter through 120 mesh, and obtain the penetrant; The anionic emulsifier is sodium tridecyl ether sulfate, and the nonionic emulsifier is octylphenol polyoxyethylene ether.
[0022] The above-mentioned dispersant is prepared by the following preparation method: 30 g of 10-hydroxystearic acid monomer was added to the reaction kettle, and melt polycondensation was carried out under the conditions of 0.02-0.09 MPa and 123-134° C. to form a polyester prepolymer; after the prepolymerization was completed, 33.2 g of docosatetraenoic acid was added to the reaction kettle, and the reaction was continued for 0.3-1 h, then discharged, cooled to 45° C. and dried to obtain a carboxyl-terminated polyester; then the carboxyl-terminated polyester was mixed with 5.86 g of 6-amino-1-hexanol, and 0.138 g of K 2 CO 3 , heat the reaction at 61-64°C for 2.5-4h, purify after the reaction is completed to obtain a polyester derivative; disperse the polyester derivative in acetone, add 3.1g of diethyl sulfate, stir the reaction at 45-51°C for 2-4h, and then purify to obtain a polyhydroxystearic acid polyester salt with a molecular weight of 3000-10000.
[0023] Table 2: each raw material and its consumption (kg) in Example 1 Examples 11-20 A water-based anti-corrosion coating, the raw materials and preparation method thereof are the same as those in Example 1, the only difference being that the amounts of the raw materials are different, as shown in the table below.
[0024] Table 3: each raw material and its consumption (kg) in Example 2 Comparative Example 1 A water-based anti-corrosion coating, the preparation method of which is the same as that of Example 1, the only difference being that the penetrant used is the fast penetrant T-30.
[0025] Comparative Example 2 A water-based anticorrosive coating, the preparation method of which is the same as that of Example 1, the only difference being that the penetrant used is the fast penetrant T-30, and the dispersant used is SPERSE P-144.
[0026] Embodiment 21 A water-based anticorrosive coating, the preparation method of which is the same as that of Example 1, the only difference being that the dispersant used is SPERSE P-144.
[0027] Embodiment 22 A water-based anticorrosive coating, the preparation method of which is the same as that of Example 1, the only difference being that the dispersant is a polyhydroxy stearic acid polyester salt, and is prepared by the following preparation method: 30 g of 12-hydroxystearic acid monomer was added to the reaction kettle, and melt polycondensation was carried out under the conditions of 0.02-0.09 MPa and 123-134° C. to form a polyester prepolymer; after the prepolymerization was completed, 33.2 g of docosatetraenoic acid was added to the reaction kettle, and the reaction was continued for 0.3-1 h, then discharged, cooled to 45° C. and dried to obtain a carboxyl-terminated polyester; then the carboxyl-terminated polyester was mixed with 5.86 g of 6-amino-1-hexanol, and 0.138 g of K 2 CO 3 , heat the reaction at 61-64°C for 2.5-4h, purify after the reaction is completed to obtain a polyester derivative; disperse the polyester derivative in acetone, add 3.1g of diethyl sulfate, stir the reaction at 45-51°C for 2-4h, and then purify to obtain a polyhydroxystearic acid polyester salt with a molecular weight of 3000-10000.
[0028] The coatings prepared in the above embodiments and comparative examples were sprayed, and the coating thickness was controlled at 1.5 mm. According to "HG4761-2014 Waterborne Polyurethane Coatings", the coatings prepared in the embodiments and comparative examples were subjected to performance testing tests, and the specific test items included: adhesion, impact resistance, water resistance, acid resistance, alkali resistance, salt water resistance and neutral salt spray resistance; according to GB / T30792-2014 "Test Method for Antimicrobial Infection of Waterborne Coatings in Cans", the coatings prepared in the embodiments and comparative examples were subjected to performance testing tests, and the test results were judged as follows: Level 0 - sterile growth; Level 1 - 1-9 cfu / dish; Level 2 - 10-99 cfu / dish; Level 3 -> 100 cfu / dish.
[0029] Table 4: Performance test results of Examples 1-10 Table 5: Performance test results of Examples 11-20 Table 6: Performance test results of Examples 21-22 and Comparative Examples 1-2 According to the data analysis of Tables 4-6, we found that the penetrant and dispersant prepared by a specific process have significant significance for improving the anti-corrosion performance of the coating of this application. When these two additives are used in combination in a compound form, the coating can still show good performance in a complex and changeable corrosive environment.
[0030] It is particularly worth mentioning that the unique quaternary ammonium salt structure in the polyhydroxy stearic acid polyester salt dispersant can effectively interact with the negative charge on the surface of the substrate to form a stable chemical bond, thereby greatly improving the adhesion between the coating and the substrate, ensuring that the coating fits tightly on the substrate. In addition, the quaternary ammonium salt structure can also significantly enhance the durability of the coating, making it more resistant to erosion and damage from the external environment.
[0031] On the other hand, the Rhodia special monomer (i.e., methacrylate phosphate monomer) contained in the penetrant has a high compatibility with the quaternary ammonium salt structure in the polyhydroxy stearic acid polyester salt dispersant in terms of chemical structure. There may be a variety of interactions between them, such as hydrogen bonds, ionic bonds, or van der Waals forces, which not only enhance the compatibility between the dispersant and the penetrant, but also promote the synergistic effect between them.
[0032] Therefore, when the above-mentioned dispersant and penetrant are compounded and used, the prepared coating can exhibit excellent anti-corrosion performance in a variety of corrosive environments.
[0033] The above are all modifications without creative contribution or solutions that obviously constitute technical inspiration that can be made to the present embodiment as needed by technical personnel in this field after reading this specification, but they should be protected by patent law as long as they are within the scope of the claims of this application.
Claims
1. A water-based anticorrosive coating, characterized in that: The raw materials used for preparation, by weight, include: 30-38 parts of waterborne polyurethane resin Acrylic emulsion 25-32 parts Filler 15-23 parts Dispersant 1-3 parts Penetrant 0.01-1.2 parts Emulsifier 0.01-1 part Defoamer 0-0.05 parts Film-forming aid 0-10 parts Other additives 0-1 part; The penetrant is prepared by the following preparation method: S1, weighing deionized water, anionic emulsifier, nonionic emulsifier, vinyl trimethoxy silane, and propylene glycol, then mixing them, and heating to 85-90° C. to obtain a kettle bottom material; S2. Deionized water, anionic emulsifier, and nonionic emulsifier are weighed separately, and after stirring and mixing, methyl methacrylate, butyl acrylate, methacrylic acid, and methacrylate phosphate monomer are added, and after stirring and mixing, an emulsion is obtained, and 5-10 wt% of the emulsion is taken out as a seed solution; S3. Add the seed liquid to the kettle bottom material at 85-90°C, add the ammonium persulfate aqueous solution dropwise after 1-2 minutes, stir and react for 10 minutes, add the remaining emulsion first, then add tert-butyl hydroperoxide, stir and react at 83-85°C for 3.5-4 hours, keep warm at 85°C for 1 hour, cool to 73°C, add the redox agent dropwise and keep warm for 20 minutes, continue to cool to below 40°C, adjust the pH value to 7-7.5, filter through 120 mesh, and obtain the product.
2. The water-based anticorrosive coating according to claim 1, wherein the raw materials used for preparation are calculated by weight and include: 35-38 parts of waterborne polyurethane resin Acrylic emulsion 28-32 parts Filler 15-23 parts Dispersant 1.5-3 parts Penetrant 0.01-0.45 parts Emulsifier 0.01-1 part Defoaming agent 0.01-0.05 parts Film-forming aid 4-10 parts Other additives 0.2-1 part.
3. The water-based anticorrosive coating according to claim 1, characterized in that: The filler is one or more of kaolin, titanium dioxide, carbon black, barium sulfate, and wollastonite; the other additives include one or more of a leveling agent, a thickener, and a pH regulator.
4. The water-based anticorrosive coating according to claim 1, characterized in that: The anionic emulsifier is one of linear fatty alcohol sodium sulfate salt, fatty alcohol ether sulfate sodium salt, tridecyl ether sodium sulfate, sodium dodecyl sulfate, fatty phosphate, and alcohol ether succinic acid monoester sodium salt containing alkylphenol polyoxyethylene ether compounds; the nonionic emulsifier is one of tridecyl alcohol ethoxylate, octylphenol polyoxyethylene ether, and isomeric alcohol ethoxylate.
5. The water-based anticorrosive coating according to claim 1, characterized in that: The dispersant is a polyhydroxy stearic acid polyester salt, and is prepared by the following preparation method: Add 10-hydroxystearic acid monomer to a reactor, and carry out melt polycondensation under the conditions of 0.02-0.09Mpa and 123-134°C to form a polyester prepolymer; after the prepolymerization is completed, add a capping agent to the reactor, continue to react for 0.3-1h, then flow out, cool and dry to obtain a carboxyl-terminated polyester; then mix the carboxyl-terminated polyester with 6-amino-1-hexanol, add an alkali metal catalyst, heat at 61-64°C for reaction for 2.5-4h, purify after the reaction is completed to obtain a polyester derivative; disperse the polyester derivative in acetone, add an alkylating agent, stir at 45-51°C for reaction for 2-4h, and then purify to obtain a polyhydroxystearic acid polyester salt.
6. The water-based anticorrosive coating according to claim 5, characterized in that: The end-capping agent is one of docosatetraenoic acid, lauric acid, and palmitic acid; the alkylating agent is one of trimethyloxonium tetrafluoroborate and diethyl sulfate; and the alkali metal catalyst is one of K2CO3 and CSF-K2CO3.
7. The method for preparing the water-based anticorrosive coating according to any one of claims 1 to 6, characterized in that: The following steps are involved: a. Mix the waterborne polyurethane resin and the acrylic emulsion, raise the temperature to 45-50°C, and stir for 30-40 minutes to obtain a mixture; b. Weigh other additives and disperse them in water to form a solution, then add fillers and polydopamine to the solution, heat to 55-60°C, stir for 50-60 minutes, and obtain a dispersion; c. Add the dispersion, penetrant and emulsifier to the mixture, stir at 45-50°C for 1.6-2h. During this process, add defoamer and film-forming aid in sequence every 15-20min, observe the number of bubbles, stop stirring, and let it stand until no bubbles are generated.
8. The method for preparing the water-based anticorrosive coating according to claim 7, characterized in that: In step c, the mass concentration of the solution is 3-10 g / L.